Rational Design of a Uranyl Metal–Organic Framework for the Capture and Colorimetric Detection of Organic Dyes. Issue 61 (1st October 2020) - Surbella, Robert G.; Carter, Korey P.; Lohrey, Trevor D.; Reilly, Dallas; Kalaj, Mark; McNamara, Bruce K.; Schwantes, Jon; Abergel, Rebecca J.
Abstract: A new uranyl containing metal–organic framework, RPL‐1 : [(UO2 )2 (C28 H18 O8 )] . H2 O (RPL for Radiochemical Processing Laboratory), was prepared, structurally characterized, and the solid‐state photoluminescence properties explored. Single crystal X‐ray diffraction data reveals the structure of RPL ‐1 consists of two crystallographically unique three dimensional, interpenetrating nets with a 4, 3‐connected tbo topology. Each net contains large pores with an average width of 22.8 Å and is formed from monomeric, hexagonal bipyramidal uranyl nodes that are linked via 1, 2, 4, 5‐tetrakis(4‐carboxyphenyl)benzene (TCPB) ligands. The thermal and photophysical properties of RPL‐1 were investigated using thermogravimetric analysis and absorbance, fluorescence, and lifetime spectroscopies. The material displays excellent thermal stability and temperature dependent uranyl and TCPB luminescence. The framework is stable in aqueous media and due to the large void space (constituting 76 % of the unit cell by volume) can sequester organic dyes, the uptake of which induces a visible change to the color of the material. Abstract : A new luminescent uranyl containing metal–organic framework, RPL‐1: [(UO2 )2 (C28 H18 O8 )] . H2 O (RPL for Radiochemical Processing Laboratory), was prepared and structurally characterized. The structure consists of interpenetrating nets with large pores (Avg. 22.8 Å) and a 4, 3‐connected tbo topology. The material exhibits high thermal and aqueous stability and due to the large void space (constituting 76 % of the unit cell by volume) can sequester organic dyes of various size and charge.